Surgical Anatomy of Temporalis Muscle Transfer with Fascia Lata Augmentation for the Reanimation of the Paralyzed Face: A Cadaveric Study - Zhang, Yi; Steinbacher, Johannes; Weninger, Wolfgang J.; Heber, Ulrike M.; Reissig, Lukas; Yildiz, Erdem; Tzou, Chieh-Han J. (Archives of Plastic Surgery, 2023)
Background The temporalis muscle flap transfer with fascia lata augmentation (FLA) is a promising method for smile reconstruction after facial palsy. International literature lacks a detailed anatomical analysis of the temporalis muscle (TPM) combined with fascia lata (FL) augmentation. This study aims to describe the muscle's properties and calculate the length of FL needed to perform the temporalis muscle flap transfer with FLA.Methods Twenty nonembalmed male (m) and female (f) hemifacial cadavers were dissected to investigate the temporalis muscle's anatomy.Results The calculated minimum length of FL needed is 7.03cm (f) and 5.99cm (m). The length of the harvested tendon is 3.16cm/± 1.32cm (f) and 3.18/± 0.73cm (m). The length of the anterior part of the temporalis muscle (aTPM) is 4.16/± 0.80cm (f) and 5.30/± 0.85cm (m). The length of the posterior part (pTPM) is 5.24/± 1.51cm (f) and 6.62/± 1.03cm (m). The length from the most anterior to the most posterior point (aTPMpTPM) is 8.60/± 0.98cm (f) and 10.18/± 0.79cm (m). The length from the most cranial point to the distal tendon (cTPMdT) is 7.90/± 0.43cm (f) and 9.79/± 1.11cm (m).Conclusions This study gives basic information about the temporalis muscle and its anatomy to support existing and future surgical procedures in their performance. The recommended minimum length of FL to perform a temporalis muscle transfer with FLA is 7.03cm for female and 5.99cm for male, and minimum width of 3 cm. We recommend harvesting some extra centimeters to allow adjusting afterward.
Keywords: facial palsy; temporalis muscle; lengthening temporalis myoplasty; fascia lata augmentation